2005
DOI: 10.1007/s00418-005-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel population of neuronal cells expressing the olfactory marker protein (OMP) in the anterior/dorsal region of the nasal cavity

Abstract: The olfactory marker protein (OMP) is expressed in mature chemosensory neurons in the nasal neuroepithelium. Here, we report the identification of a novel population of OMP-expressing neurons located bilaterally in the anterior/dorsal region of each nasal cavity at the septum. These cells are clearly separated from the regio olfactoria, harboring the olfactory sensory neurons. During mouse development, the arrangement of the anterior OMP-cells undergoes considerable change. They appear at about stage E13 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 33 publications
1
48
1
Order By: Relevance
“…Axonal projection maps in the olfactory bulb are characteristic of each type of olfactory sensory neuron. The axonal projections of the Grueneberg ganglion have only recently been associated with the olfactory system (Fleischer et al, 2006a;Fuss et al, 2005;Koos and Fraser, 2005;Roppolo et al, 2006;Storan and Key, 2006). They converge in the olfactory bulb and are part of a group of glomeruli called the necklace glomeruli (Shinoda et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Axonal projection maps in the olfactory bulb are characteristic of each type of olfactory sensory neuron. The axonal projections of the Grueneberg ganglion have only recently been associated with the olfactory system (Fleischer et al, 2006a;Fuss et al, 2005;Koos and Fraser, 2005;Roppolo et al, 2006;Storan and Key, 2006). They converge in the olfactory bulb and are part of a group of glomeruli called the necklace glomeruli (Shinoda et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a cluster of neurons-henceforward referred to as Grueneberg ganglion neurons (GGNs)-that express olfactory marker protein (OMP) and project their axons to a small number of glomeruli in the caudal main olfactory bulb (Fuss et al, 2005;Koos and Fraser, 2005;Fleischer et al, 2006;Roppolo et al, 2006;Storan and Key, 2006). Interestingly, these glomeruli are near the necklace glomeruli innervated by olfactory sensory neurons expressing the receptor guanylyl cyclase GC-D (Fülle et al, 1995;Juilfs et al, 1997;Leinders-Zufall et al, 2007;Walz et al, 2007; for review, see Munger et al, 2009), and both GC-D-expressing neurons and GGNs express elements of a cGMP second messenger pathway, including the cGMP-specific cyclic nucleotide-gated channel CNGA3 and the cGMP-stimulated phosphodiesterase PDE2 (Juilfs et al, 1997;Meyer et al, 2000;Leinders-Zufall et al, 2007;Fleischer et al, 2009;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the blend of mouse APs induces calcium transients specifically in the neurons of the Grueneberg ganglion (GG), an olfactory subsystem present at the tip of the nose, close to the opening of the naris (21,(23)(24)(25)(26)(27). The mouse GG is an arrowshaped neuronal structure 750-1,000 μm in length.…”
mentioning
confidence: 99%
“…The GG displays multimodal properties (21,(30)(31)(32)(33) and starts developing around embryonic day 16. Contrary to the other olfactory subsystems, the GG appears to be complete and functional at birth (24)(25)(26)(27)(28), ensuring immediate AP sensing and increasing chances of survival in the wild. An intact GG is necessary to observe the fearful behavior of the recipient animals in the presence of APs (21).…”
mentioning
confidence: 99%